1998
DOI: 10.1016/s1074-7613(00)80588-9
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphotoxin β Receptor Controls Organogenesis and Affinity Maturation in Peripheral Lymphoid Tissues

Abstract: Lymphotoxin beta receptor (LTbetaR)-/- mice were created by gene targeting. LTbetaR-/- mice lacked Peyer's patches, colon-associated lymphoid tissues, and all lymph nodes. Mucosa patrolling alphaEbeta7high integrin+ T cells were virtually absent. Spleens lost marginal zones; T/B cell segregation and follicular dendritic cell networks were absent. Peanut agglutinin+ cells were aberrantly detectable around central arterioles. In contrast to TNF receptor p55-/- mice, antibody affinity maturation was impaired. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
618
3
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 674 publications
(648 citation statements)
references
References 56 publications
25
618
3
2
Order By: Relevance
“…LTa À/À , LTb À/À and LTbR À/À mice display severe developmental defects in lymph node and Peyer's patch neogenesis, a disorganized lymphoid microarchitecture and lack of mature follicular dendritic cells (Pfeffer et al, 1993;De Togni et al, 1994;Koni et al, 1997;Futterer et al, 1998;Ngo et al, 1999). In addition, LTa À/À and LTbR À/À mice show inflammatory disorders in nonlymphoid organs (for example, lung, liver, kidney; (Fu et al, 1997(Fu et al, , 2000Fu and Chaplin, 1999;Chin et al, 2003).…”
Section: Ltbr Activation and Nf-jb Signalingmentioning
confidence: 99%
“…LTa À/À , LTb À/À and LTbR À/À mice display severe developmental defects in lymph node and Peyer's patch neogenesis, a disorganized lymphoid microarchitecture and lack of mature follicular dendritic cells (Pfeffer et al, 1993;De Togni et al, 1994;Koni et al, 1997;Futterer et al, 1998;Ngo et al, 1999). In addition, LTa À/À and LTbR À/À mice show inflammatory disorders in nonlymphoid organs (for example, lung, liver, kidney; (Fu et al, 1997(Fu et al, , 2000Fu and Chaplin, 1999;Chin et al, 2003).…”
Section: Ltbr Activation and Nf-jb Signalingmentioning
confidence: 99%
“…Lymph nodes are located throughout the body to monitor the draining fluids and migrating lymphocytes for pathological changes (Lo et al, 2006;Mebius, 2003). The ltbr -/-mice demonstrated that lymphotoxin-β receptor (LTβR) signaling critically regulates lymph node formation (Futterer et al, 1998;Rennert et al, 1998). During early embryogenesis, membrane bound LTα 1 β 2 on the hematopoietically derived lymph tissue inducer cells (LTIC) signal through LTβR present on the stromal organizer cells to initiate lymph node development.…”
Section: Secondary Lymphoid Organ Development Via the Ltβrmentioning
confidence: 99%
“…Studies in mutant mice and blocking experiments have identified a key requirement for TNF-family members, mainly lymphotoxin α1β2 (LTα1β2), and to some extent TNF, in the development and organization of lymph nodes and spleen microarchitecture [25][26][27][28]. Binding of LTα1β2 and TNF to their respective receptors, LTβR and TNFR1, induces the expression of chemokines and adhesion molecules, which directly mediate lymphocyte migration and homing [29].…”
Section: Light Creates Lymphoid-like Tissues Inside the Tumor To Imprmentioning
confidence: 99%